PS01.058: OLDER AGE AND DEMENTIA MIGHT BE CONSIDERED BACKGROUND FACTORS OF BLEEDING FROM EROSIVE REFLUX ESOPHAGITIS WITH ESOPHAGEAL ULCER. (14th September 2018) - Kato, Tomohiro; Uno, Yukari; Ichikawa, Hironao; Iwasa, Yuhei; Nakayama, Chiemi; Ogiso, Hideyuki; Okuno, Mitsuru; Suzuki, Yusuke; Ogiso, Tomio; Mukai, Tsuyoshi; Hayashi, Hideki; Sugiyama, Akihiko; et al.
Abstract: Background: Hematemesis is one of the most eventful complications in patients with reflux esophagitis (RE). But bleeding is not observed in all patients who have RE with esophageal ulcer. We retrospectively studied the association of bleeding with background factors in patients with RE with esophageal ulcer. Methods: Between January 2013 and January 2018, 30 patients were endoscopically diagnosed as RE with Los Angeles classification D (LA-D). These 30 patients were enrolled in our study. Fifteen of them were suddenly admitted to our hospital because the RE exhibited bleeding (B-group). Patients with Mallory-Weiss syndrome, peptic ulcers, and any malignancies were excluded as possible sources of the bleeding. Bleeding was not observed in the remaining 15 RE patients (NB-group). In these 30 patients, we retrospectively studied the relations between the bleeding and the following background factors: age, gender, body mass index (BMI), esophageal hiatal hernia, endoscopical atrophy of the gastric mucosa which is related to the secretion of gastric juice, cognitive decline (so called dementia), diabetes mellitus, and drugs (NSAIDs, PPI). Results: The B-group included 5 males and 10 females. The NB-group also included 5 males and 10 females. The mean age of the B-group was 81.7 ± 8.2 (M ± SD) yrs, which was statistically ( P  < 0.05) greater than that of the NB-group, which was 71.5 ± 11.0 yrs. Older age, larger esophageal hiatal hernia, and cognitive decline (so-called dementia) were significantly ( P  < 0.05) associated with bleeding on logistic regression analysis. Multiple logistic regression analysis showed that older age and dementia were significantly ( P  < 0.05) associated with bleeding. Conclusion: It is well known that esophageal hiatal hernia is a major factor in erosive RE, such as RE with LA-D. On the other hand, it was speculated that older RE patients and those with cognitive decline could not easily explain their RE complaints, and their condition might be left unattended for long periods. This lack of attention may result in sudden bleeding in patients with non-treated RE. Further studies are needed. Disclosure: All authors have declared no conflicts of interest.